China's Selective Two-Child Policy and Its Impact on the Marriage Market - Di Lu (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper analyzes the effects of the earlier selective two-child policy (TCP) in the 1990s (both parents have to be only children) to explore the impacts of this relaxation on the marriage market as well as the fertility effect due to the marriage choice distortion. By using a difference in differences (DID) design in a subhazard model with competing risks, the results show that the subhazard ratio is 355.06% higher and this treatment effect is significant at a 1% level. The results suggest that the selective TCP increased the probability of the treatment group of choosing an only-child spouse rather than marrying a spouse with siblings or a spouse belonging to an ethnic minority. The marriage effect is stronger in urban areas where OCP was previously implemented more rigorously. The probability of giving birth to a second child is also positive and significant in a DID design, which implies that the fertility preference is binding under the OCP.
Keywords: J12; J13; C41; 330; China's two-child policy; marriage distortion; subhazard model; fertility effect